1993
DOI: 10.1007/bf03009609
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane anaesthesia for one-lung ventilation with PEEP to the dependent lung in sheep: effects on right ventricular function and oxygenation

Abstract: This study was undertaken to examine the effect of sevoflurane on right ventricular function, the safety of sevoflurane for onelung ventilation and the effects of PEEP (positive end-expiratory pressure) to the dependent lung in this model [1195][1196][1197][1198][1199][1200]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Minimally invasive surgery techniques, including thoracoscopy, are quickly gaining ground in human and veterinary medicine. Until recently, few studies were available about the applicable ventilation techniques for anaesthesia of dogs, pigs, sheep and horses during thoracoscopy (Fujita et al., 1993; Jones et al., 1993; Faunt et al., 1998; Vachon and Fischer, 1998; Peroni et al., 2000). Thoracoscopy requires general anaesthesia in dogs, sheep and pigs, whereas the technique can be performed in sedated standing horses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimally invasive surgery techniques, including thoracoscopy, are quickly gaining ground in human and veterinary medicine. Until recently, few studies were available about the applicable ventilation techniques for anaesthesia of dogs, pigs, sheep and horses during thoracoscopy (Fujita et al., 1993; Jones et al., 1993; Faunt et al., 1998; Vachon and Fischer, 1998; Peroni et al., 2000). Thoracoscopy requires general anaesthesia in dogs, sheep and pigs, whereas the technique can be performed in sedated standing horses.…”
Section: Discussionmentioning
confidence: 99%
“…During OLV selective ventilation of one lung is applied for which specific intubation, including double‐lumen tubes, endobronchial intubation, or bronchial blockers, is necessary. Positioning is technically difficult in dogs and sheep (Muneyuki et al., 1983; Fujita et al., 1993; Cantwell et al., 2000). Due to malpositioning (up to 30%) in men routine bronchoscopy after double‐lumen tube or bronchial blocker placement is certainly recommended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No differences between isoflurane and sevoflurane were detected. 15 They concluded that, although sevoflurane caused a dose-dependent depression of right ventricular function, it can be safely used during OLV. We compared the effects on oxygenation of isoflurane or sevoflurane in humans.…”
Section: Discussionmentioning
confidence: 99%
“…(19)(20)(21) Sevoflurane causes a dose-dependent depression of right ventricular function. (22) Propofol is believed to cause a reduction in systolic and diastolic arterial pressures by lowering SVRI and afterload. (23) Some studies on people and animals showed that it had no influence on CI, (23)(24)(25) while in others it caused a reduction in CI.…”
Section: Discussionmentioning
confidence: 99%